Influencia del clima en el crecimiento longitudinal y radial de Q. ilex ssp. ballota L. y Q. faginea Lam. EN EL SISTEMA IBERICO ARAGONES - Corcuera, L; CAMARERO, J J; Gil-Pelegrín, E (III Congreso Forestal Español, 2001)
Climate influence (precipitation and temperature) on primary growth (annual growth length) and secondary growth (ring width and ring surface) of Quercus ilex ssp. ballota L. (evergreen and diffuse-porous species) and Q. faginea Lam. (decidious and ring-porous species) is studied. Samples were taken from a coppice in Sierra de Santa Cruz, Cubel, Zaragoza. Both species show lesser longitudinal and radial growth in drought years. A positive and significant relationship between precipitation and secondary growth and a negative and significant relationship between high summer temperatures and secondary growth were observed. Primary and secondary growth in 1993 and previous years mirror foliage desiccation of Q. ilex in 1993.
Keywords: climate; primary growth; Q. faginea; Q. ilex ssp. ballota; secondary growth